A Novel Hammer-Shaped UWB Antenna with Triple Notched-Band for Rejecting RLS, WLAN and XSCS bands - Mewara, H. S.; Jhanwar, D.; Sharma, M. M.; Deegwal, J. K. (Advanced Electromagnetics, 2017)
A novel hammer-shaped UWB printed antenna with triple notched stop bands is presented and fabricated on FR-4 substrate with size of 40×40×1.6 mm3. The proposed antenna is composed of hammer-shaped patch with C-shaped slot, U-shaped slot on feed line, and inverted stepped notch and bevel edges with pair of L-shaped slots in partial ground plane. The fabricated antenna is tested and obtained impedance bandwidth 2.89 ̶ 11.6 GHz with three notched stop bands 3.15 ̶ 3.7 GHz, 5.45 ̶ 6.8 GHz, and 7.5 ̶ 8.8 GHz, for radiolocation system (RLS), wireless local area networks (WLAN), and X-band satellite communication system (XSCS) bands, respectively. Moreover, the antenna result shows omnidirectional radiation pattern, average gain of 3.10 dBi over the whole UWB band except at the notched frequency bands.